Основные этапы создания бронетанковой техники в Украине (1990-2011 годы) - Борисюк, М. Д. (НТУ "ХПИ", 2012)
Показано розвиток танкобудівної галузі України за період незалежності України і роль КП ХКБМ у створенні сучасних зразків танків та легко броньованої техніки.

This report shows the development of the Ukrainian tank-building industry and the role of KMDB in making the modern models of tanks and lightly armored vehicles.
Main stages of armored vehicles in Ukraine (1990–2011 years)
Keywords: танкостроение; бронетехника; бронетанковая техника; боевые бронированные машины; танки